2016
DOI: 10.1016/j.isprsjprs.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

An automated, open-source pipeline for mass production of digital elevation models (DEMs) from very-high-resolution commercial stereo satellite imagery

Abstract: a b s t r a c tWe adapted the automated, open source NASA Ames Stereo Pipeline (ASP) to generate digital elevation models (DEMs) and orthoimages from very-high-resolution (VHR) commercial imagery of the Earth. These modifications include support for rigorous and rational polynomial coefficient (RPC) sensor models, sensor geometry correction, bundle adjustment, point cloud co-registration, and significant improvements to the ASP code base. We outline a processing workflow for $0.5 m ground sample distance (GSD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
546
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 534 publications
(557 citation statements)
references
References 35 publications
10
546
0
1
Order By: Relevance
“…DEMs are increasingly available at high resolution for ice surfaces [4,16,18,20], and reproducible, accurate methods of extracting surface meltwater channels are necessary for quantifying their temporal and spatial characteristics. Flow routing has numerous advantages for delineating meltwater channels; however, previous research by Yang et al (2015) [34] on the use of flow routing over moderate-resolution ice surface DEMs found that (1) automated sink preservation thresholds missed over half of mapped moulins and resulted in significantly overestimated drainage network extent; (2) mapped channel networks could be replicated by flow routing with match rates in excess of 85% when a 600 m buffer was applied; (3) less than 40% of the FR drainage network did not match the mapped drainage network, leading to the conclusion that these channels were miscoded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DEMs are increasingly available at high resolution for ice surfaces [4,16,18,20], and reproducible, accurate methods of extracting surface meltwater channels are necessary for quantifying their temporal and spatial characteristics. Flow routing has numerous advantages for delineating meltwater channels; however, previous research by Yang et al (2015) [34] on the use of flow routing over moderate-resolution ice surface DEMs found that (1) automated sink preservation thresholds missed over half of mapped moulins and resulted in significantly overestimated drainage network extent; (2) mapped channel networks could be replicated by flow routing with match rates in excess of 85% when a 600 m buffer was applied; (3) less than 40% of the FR drainage network did not match the mapped drainage network, leading to the conclusion that these channels were miscoded.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrologically, supraglacial meltwater channels influence the spatial and temporal distribution of surface water inputs to en-and sub-glacial hydrological systems [3,[11][12][13], which in turn have been shown to influence glacier and ice sheet dynamics (e.g., [3,14,15]). This recent and growing interest has been concurrent with a growing availability of high-resolution remotely sensed imagery and topographic data of ice surfaces [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was created using the AMES stereo-pipeline (Shean et al, 2016) and the processing parameters that were used in Marti et al (2016). The two SPOT5 DEMs agency (Korona et al, 2009).…”
Section: Geodetic Mass Balancementioning
confidence: 99%
“…The satellite stereo images are showing the attractive prospects in dense image matching area. Thus since recent years, a lot of researchers have done experiments on dense image matching, DSM generation and 3D reconstruction with high resolution satellite imagery (d 'Angelo and Reinartz, 2011;Wohlfeil et al, 2012;Franchis et al, 2014;Gong and Fritsch, 2016;Ghuffar, 2016;Shean et al, 2016;Rita et al, 2017). Among various dense image matching methods, SGM method is a popular and efficient way.…”
Section: Introductionmentioning
confidence: 99%